Effectiveness Of Vessel Traffic Service Utilization By Commercial Vessels In Sorong Port - Haryanto, Dwi; Setiyono, Muji; Irfandi H, M. Adam (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
This research aims to expolarate the utilisation of vessel traffic service (vts) in sorong waters by commercial vessels on the security and safety of shipping in sorong Port waters by knowing the effectiveness of the implementation of vts on its function and operation and knowing the suitability of services to applicable regulations. This research analyses the service procedures and reports of the implementation of VTS Sorong using qualitative descriptive methods, parsing data based on the results of observations, interviews and documentation. This research shows the data of commercial vessels using the vessel traffic service (VTS) in 2023, categorises the services into three services (incoming vessels, outgoing vessels and passing vessels), presents a graph and the percentage of services per month from the three service categories to the overall service. The results in this study explain that at the port of Sorong the use of ship traffic services has been effective, there are 9430 services at VTS Sorong in 2023, the most services are carried out in October with 924 services and the most used service category is by passing ships as much as 38%. There are several obstacles in the implementation of services at VTS Sorong, good coordination is needed between each related stakeholder in an effort to maintain shipping safety and security in these waters. Keywords: Vessel Traffic Service, Vts, Maritime, Ship Service